Traditional Sami woman's cap and shawl ... - Campbell, Sandy (University of Alberta Library, 2005)
This is a traditional Sami woman's cap and shawl from the back. The shawl is usually pinned at the front with and elaborate silver pin. The Sami flag sits on the table in front of the woman. ...